Ok, so for a) we have

(f o g)(3) = f(g(3)) (function composition)

= f(2*3 + 4) (by defn of g)

= f(10) (simplifying)

= 10^2 - 3*10 + 5 (by defn of f now)

= 75.

I'm sure you can do b) now - it's the same thing, just this time you won't end up with a number, you'll end up with something involving x's.

Swap the f(x)'s and x's, like so:

x = 4*f(x) - 8.

Now we just solve for f(x) again, ie,

f(x) = (x + 8)/4.

You can check it's the inverse by evaluating f(f^-1(a)) and f^-1(f(a)). In both cases we want to end up with just a.

Hope that helps.